ALALIYA SÓYLEW NUQSANÍ BOLǴAN BALALARDA SÓYLEW ISKERLIGIN QÁLIPLESTIRIW USÍLLARÍ - Ajimova, Z. (SCIENCE and SOCIETY, 2023)
The article tells about children with alalia speech disorder, about their differences in speech and motor development, and about ways to eliminate their shortcomings with speech therapy-corrective exercises.